Macroeconomics and bank-specific determinants of profitability in Malaysian Banking sector / Dk Nur Farah Ain Natasha Ag Abdullah - Ag Abdullah, Dk Nur Farah Ain Natasha (2019)
The present study investigates the bank-specific and macroecnomic as a determinants of bank profitability. The motive of this paper is to identify the bank performance from the bank-specific and macroeconomics factors whereas indicates their profitability in financial institution which is banking sector that listed in Bursa Malaysia. The internal factors that will affect the generated profits which is bank size and capital adequacy while external factors is inflation rate and GDP growth rate that represent the economic condition. The objective of this study is to examine the relationship between the bank size, capital adequacy, GDP growth rate and inflation rate towards the return on asset of the bank that listed in Bursa Malaysia. The stata panel data was employed to test the result. The empirical finding have found that GDP growth rate has a positive and significant relationship with return on asset. Apart from that, other variable which is capital adequacy that using equity ratio to measures the financial performance shows a positive correlated but not significant relationship with return on asset in banking sector in Malaysia. However, the bank size that indicates total asset and inflation rate shows a negative and insignificantly relationship with return on asset.